1994
DOI: 10.1021/ma00104a006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Regiochemical and Stereochemical Errors on the Course of Isotactic Propene Polyinsertion Promoted by Homogeneous Ziegler-Natta Catalysts

Abstract: The effects of regiochemical and stereochemical errors on the kinetic course of isotactic propene polyinsertion promoted by two typical homogeneous metallocene catalysts are analyzed in detail. It is shown, in particular, that occasional regioirregular 2,1 insertions not only slow down chain propagation to a substantial extent-as already reported in a preliminary communication-but also practically inhibit chain transfer to the monomer and to the aluminum alkyl cocatalyst. Active centers bearing a growing chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
158
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(167 citation statements)
references
References 5 publications
9
158
0
Order By: Relevance
“…[18,20] The low selectivity of this catalysts would be due to a low ratio k ins (insertion constant)/k epim (epimerization constant). Busico et al found a value of 70 l/mol for EtInd 2 ZrCl 2 / MAO and 8 l/mol for Et(IndH 4 ) 2 ZrCl 2 .…”
Section: Discussionmentioning
confidence: 99%
“…[18,20] The low selectivity of this catalysts would be due to a low ratio k ins (insertion constant)/k epim (epimerization constant). Busico et al found a value of 70 l/mol for EtInd 2 ZrCl 2 / MAO and 8 l/mol for Et(IndH 4 ) 2 ZrCl 2 .…”
Section: Discussionmentioning
confidence: 99%
“…It is formed after the regioirregular 2,1-insertion of a propylene molecule into a Zr-C bond in metallocene-catalyzed propylene polymerization reactions. 36 This center also has the methyl group in the ␤-position to the metal atom, Zr-CH(CH 3 )-CH 2 -polymer, and can involve coordination between its H atom and the vacancy at the Zr atom.…”
Section: A Strongly Agostic Co Complex [Cpco-mentioning
confidence: 99%
“…Comparison of the activitiy curves between an 1-octene and a propylene prepolymerized catalyst system 1 and the untreated system lower molecular weights of the produced polymers due to chain transfer reactions. Additionally, the activity is enhanced dramatically because of the multiplication of the total number of active centers [8][9][10] . This activation effect was used to get a more comprehensive insight into the early polymerization stages.…”
Section: Activation Experiments Using Hydrogenmentioning
confidence: 99%